2017
DOI: 10.5830/cvja-2016-047
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and arterial stiffness in pre-eclampsia demonstrated by the EndoPAT method

Abstract: SummaryObjectivesThe EndoPAT method has been used as a noninvasive method for assessing endothelial function in several non-pregnant populations. We investigated its possible use in assessing endothelial dysfunction in pre-eclampsia.MethodsTwo hundred and fifteen participants were recruited and grouped as pre-eclamptic cases (105) and normotensive controls (110). Endothelial function and arterial stiffness were measured as reactive hyperaemia index and augmentation index, respectively, using the EndoPAT 2000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
20
0
2
Order By: Relevance
“…Multiple investigations of PE reveal that poor placentation is linked to endothelial dysfunction, endoplasmic reticulum stress, apoptosis, and most importantly, OS of the placenta. [23][24][25] Inhibition of the p38MAPK signaling pathway could reduce OS both in vivo and in vitro in PE was verified. 17 The purpose of the present study is to assess the roles of NCAM1d in OS in pregnancy complicated by PE with the participation of the p38MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Multiple investigations of PE reveal that poor placentation is linked to endothelial dysfunction, endoplasmic reticulum stress, apoptosis, and most importantly, OS of the placenta. [23][24][25] Inhibition of the p38MAPK signaling pathway could reduce OS both in vivo and in vitro in PE was verified. 17 The purpose of the present study is to assess the roles of NCAM1d in OS in pregnancy complicated by PE with the participation of the p38MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Multiple investigations of PE reveal that poor placentation is linked to endothelial dysfunction, endoplasmic reticulum stress, apoptosis, and most importantly, OS of the placenta . Inhibition of the p38MAPK signaling pathway could reduce OS both in vivo and in vitro in PE was verified .…”
Section: Discussionmentioning
confidence: 89%
“…The majority of studies on the assessment of vascular endothelial function using peripheral arterial tonometry and EndoPAT 2000 device was performed in women during gestation with the aim to describe potential association between vascular endothelial dysfunction and pregnancy-induced hypertension or preeclampsia [20,23,[50][51][52][53], sleep-disordered breathing in women with preeclamptic toxaemia [54], and smoking status [55].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that women with preeclampsia show impaired endothelial function (significantly low RHI scores [OR: 1.70, 95% CI: 1.04-3.61]) compared with normotensive pregnant women (OR: 1.81, 95% CI: 1.18-4.62; p < 0.05). 8 Although these results seemed to confirm endothelial dysfunction in preeclampsia women, they only evaluated women at the time of diagnosis. They did not study the predictive ability of assessments of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 92%
“…Although this method has been used extensively in nonpregnant patients, few studies have examined its utility in predicting preeclampsia. 6,8,9 In one retrospective study, researchers measured postdelivery endothelial function of women who experienced preeclampsia to determine whether residual endothelial dysfunction may contribute to future cardiovascular issues, and found that there was persistent microcirculatory dysfunction in women with previous pregnancies complicated by preeclampsia. 4,5 Whether this technique can be used to predict preeclampsia in women with high-risk factors, by detecting early signs of endothelial dysfunction, is currently not known.…”
mentioning
confidence: 99%